1990
DOI: 10.21000/jasmr90010243
|View full text |Cite
|
Sign up to set email alerts
|

The Use of CO2 Coulometry in Differentiating and Quantifying the Carbonate Phases in the Coal-Bearing Strata of Western Pennsylvania: Its Applicability in Interpreting and Modifying Neutralization Potential (NP) Measurements

Abstract: CO 2 coulometry is a rapid, highly accurate technique which can be used to determine the carbonate carbon contents of coals and associated overburdens. The rate at which the co 2 is evolved during the acid digestion process is a function of which carbonate phases are present. Calcite and dolomite reaction times are approximately six to eight minutes under the conditions described herein, with the maximum change in reaction rates occurring between two and four minutes. Siderite requires a lengthy 10 to 15 minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…The majority of the carbonate present was associated with samples 170 -175. CO 2 coulometry data, as interpreted and discussed by Morrison et al (1990) indicated that the dominant carbonate phase present in these overburdens was siderite. This interpretation was also verified using x-ray diffraction.…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…The majority of the carbonate present was associated with samples 170 -175. CO 2 coulometry data, as interpreted and discussed by Morrison et al (1990) indicated that the dominant carbonate phase present in these overburdens was siderite. This interpretation was also verified using x-ray diffraction.…”
mentioning
confidence: 79%
“…Further data to support the observation that l1n is contained in siderite as a crystal chemical substituent was obtained from a siderite concretion (not from this mine site), {Morrison et al 1990) for which 40 grains of siderite were analyzed for Fe, Mn, Mg and Ca. These data, Table 1, show an average Mn-substitution of 3500 ppm which is equated to a molar substitution of: (Fe.s6Mg.02Ca.1Mn.01)C0 3 • Table 2 further supports the presence of a nearly constant, within experimental error, concentration of Mn in this 13.5 foot sequence of black shales.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…We are aware of only one study that has attempted to quantify various fractions of carbonate using coulometric titration where the CO2 evolved in the reaction with acid was continuously monitored (Morrison et al, 1990). Although Morrison et al (1990) were able to distinguish and quantify siderite from the total carbonate in the rock samples used in their study, they were not successful in distinguishing calcite from dolomite. Our aim was to overcome the limitations in Morrison et al (1990) by grounding the description of the reaction rates of calcite and dolomite in a more theoretically based kinetic model.…”
mentioning
confidence: 99%